2010
DOI: 10.1183/09031936.00179409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiling and epidermal growth factor receptor-directed therapy in nonsmall cell lung cancer

Abstract: The principle of preferentially selecting patients most likely to benefit from therapy according to their genetic profile has led to substantial clinical benefit in some tumour types, and has potential to considerably refine treatment in advanced nonsmall cell lung cancer (NSCLC). Effective, reliable use of molecular biomarkers to inform clinical practice requires the standardisation of testing methods and careful assessment of biomarkers’ predictive and prognostic value.Although a number of studies have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 97 publications
(79 reference statements)
0
19
0
1
Order By: Relevance
“…However, these analyses were retrospective and limited by sample availability. It has since been established that EGFR mutation status influences the efficacy of EGFR tyrosine kinase inhibitors in both first-and second-line settings [15][16][17][18].…”
mentioning
confidence: 99%
“…However, these analyses were retrospective and limited by sample availability. It has since been established that EGFR mutation status influences the efficacy of EGFR tyrosine kinase inhibitors in both first-and second-line settings [15][16][17][18].…”
mentioning
confidence: 99%
“…However, the low EGFR mutation rate (n=5, 5.6%) indicates that this molecular alteration only minimally impacts the treatment efficacy, even in arm E. DCR and PFS were not affected by tumour KRAS mutation status (table 2). Given that KRAS mutations were observed in only seven of the 41 tumours in arm E patients, this finding cannot account for erlotinib's low efficacy in mucinous patients [30]. TUBB3 and MSH2 are markers that have previously been revealed to demonstrate positive expression in adenocarcinoma [21,22].…”
Section: Discussionmentioning
confidence: 92%
“…For lung cancer the only biomarkers reaching a significant predictive effect for a targeted therapy, as compared with chemotherapy, are epidermal growth factor receptor (EGFR) mutations [9,10] and anaplastic lymphoma kinase (ALK) rearrangements [11] in oncogene-driven tumours, representing ,15% of metastatic NSCLC. Indeed, five prospective phase III trials in Asian and Caucasian populations clearly showed that EGFR kinase inhibitors (erlotinib, gefitinib or afatinib) were superior to cisplatin-based chemotherapy in the first-line setting in patients with EGFR activation mutations [9,[12][13][14][15].…”
Section: Issues For Predictive Biomarkers In Nsclcmentioning
confidence: 99%